"Big Tigers, Big Data": Learning Social Reactions to China's Anticorruption Campaign through Online Feedback. (24th October 2017) - Zhu, Jiangnan; Huang, Huang; Zhang, Dong
Abstract : This article examines the effect of campaign‐style anticorruption efforts on political support using the case of China's most recent anticorruption drive, which stands out for its harsh crackdown on high‐ranking officials, known as "big tigers." An exploratory text analysis of more than 370, 000 online comments on the downfall of the first 100 big tigers, from 2012 to 2015, reveals that public support for the top national leader who initiated the anticorruption campaign significantly exceeded that afforded to anticorruption agencies and institutions. Further regression analyses show that support for the leaders with respect to intuitions increased with the tigers' party ranking. Findings suggest that while campaign‐style enforcement can reinforce the central authority and magnify support for individual leaders, it may also marginalize the role of legal institutions crucial to long‐term corruption control .